PO.5.114 Online education significantly improved rheumatologists' knowledge of the burden of lupus nephritis and appropriate treatment strategies for patients. (27th September 2022) - Bell, E; Calle, M; Lightstone, L
Abstract : Background/purpose: Lupus nephritis (LN) is the most common severe manifestation of SLE and can progress to end stage kidney disease within 15 years of diagnosis in up to 25% of patients. It is important that rheumatologists understand the pathogenesis of LN, the substantial burden of this condition and best practice in improving long-term outcomes for patients using appropriate treatment strategies. Methods: Rheumatologists participated in an online video activity entitled ''An Update on Lupus Nephritis' (launched 03 June 2021, data collection by March 2022). Educational effect was assessed using a repeated-pair design, pre-/post-assessment. A paired samples t-test was conducted for significance testing on overall average number of correct responses and for confidence rating. Cohen's d with correction for paired samples estimated the effect size of the education on number of correct responses (<0.20 modest, .20-.49 small, .59-.79 moderate, ≥.80 large). A series of McNemar's tests were conducted at the question level (5% significance level, P <0.05). Results: Rheumatologists (n=246) significantly improved their knowledge of the burden of LN (P <0.001), and treatment strategies for LN (P <0.05) Rheumatologists had a high baseline level of knowledge regarding the role of kidney biopsy in SLE patients showing signs of kidney involvement The average percentage of questions answered correctly increased by 32% (P <0.001) 98% reported that the education will improve their performance, resulting in improved patient outcomes Post-activity, 28% of rhematologists reported increased confidence in managing patients with SLE and LN Overall, 95% of rheumatologists experienced an increase or reinforcement of knowledge (pie chart); confidence improvements were larger for those who had an improvement/reinforcement of knowledge (right hand graph) compared with those who were unaffected Conclusions: Participation in this online activity significantly improved rheumatologists' understanding of LN in patients with SLE. These results suggest that further education on LN would be beneficial for rheumatologists to embed knowledge of LN, increase awareness of screening for LN, and minimize the potential long-term consequences of LN for patients. Acknowledgement: Supported by an independent educational grant from GlaxoSmithKline